Pengaruh Perselisihan dalam Gaya Evaluasi Kinerja Anggaran terhadap Kinerja : Tekanan Kerja dan Kepuasan Kerja sebagai Variabel Mediasi - Maulana kamal; Ainun Na’im (The Indonesian Journal of Accounting Research, 2013)
This paper extends previous work in the area of supervisory style as it pertains to the use of budgetary information for performance evaluation. Previous research has focused exclusively on the superior's budgetary performance evaluation style. This study focused on both superior's perceived and the subordinate's preferred budgetary performance evaluation styles. When subordinate's preferred style disagrees with the superior's perceived style, this disagreement is hypothesized to lead to the subordinate's and superior's feeling higher job-related tension and lower job satisfaction.Eighty-nine managers and staffs from a cross-section of department in Indonesia manufacturing companies paricipated in this study. The results support the hypothesized relations. This study also examines two mediating models, (1) job-related tension that nay mediate the relationship between disagreement in budgetary performance evaluation style and performance, and (2) job satisfaction that may mediate the relationship between disagreement and performance. The result indicate that only job satisfaction mediates the relationship beween disagreement in budgetary performance evaluation style and performance. Finally, a structure equation model is used to determine the overall impact of disagreement in budgetary performance evaluation style on job-related tension, job satisfaction and performance.